ANALISIS TREN SEBAGAI PENILAIAN KINERJA KEUANGAN PADA PT INDOFOOD SUKSES MAKMUR Tbk: - Titik Purwaningtyas; Hamizar Hamizar; Jaenudin Akhmad; Taty Noorhayati (JURNAL LENTERA AKUNTANSI, 2025)
The purpose of this study is to determine the financial performance of PT Indofood Sukses Makmur Tbk based on the company's balance sheet and income statement using trend analysis. The research method used in this study is a quantitative descriptive method. The quantitative descriptive method is a research method that aims to describe and analyze quantitative data about the financial performance of PT Indofood Sukses Makmur Tbk. Techniques for collecting data include library research and field research. The results of this study are based on the analysis of the financial statements of PT Indofood Sukses Makmur Tbk, namely the balance sheet and income statement for the period 2022 to 2024, in which total assets, equity, sales and operating income, current year profit tended to increase, and good management of cost of goods sold and revenue. As a result, it can be concluded that the financial performance of PT Indofood Sukses Makmur Tbk is quite good. However, the company needs to effectively manage its liabilities and selling, general, and administrative expenses to maintain financial stability, ensure smooth operations, and increase profitability.